Proprioceptors of the human pericardium - Piermaier, Lea M.; Caspers, Svenja; Herold, Christina; Wolf-Vollenbröker, Michael; Brzoska, Patrick; Bechler, Eric; Filler, Timm J. (Basic research in cardiology, 2024)
In the human organism, all functions are regulated and, therefore, require a feedback mechanism. This control involves a perception of the spatial tensile state of cardiac tissues. The presence and distribution of respective proprioceptive corpuscles have not been considered so far. Therefore, a comprehensive study of the entire human fibrous pericardium was conducted to describe the presence of proprioceptors, their density, and distribution patterns. Eight human pericardial specimens gained from our body donation program were used to create a three-dimensional map of proprioceptors in the pericardium based on their histological and immunohistochemical identification. The 3D map was generated as a volume-rendered 3D model based on magnetic resonance imaging of the pericardium, to which all identified receptors were mapped. To discover a systematic pattern in receptor distribution, statistical cluster analysis was conducted using the Scikit-learn library in Python. Ruffini-like corpuscles (RLCs) were found in all pericardia and assigned to three histological receptor localizations depending on the fibrous pericardium’s layering, with no other corpuscular proprioceptors identified. Cluster analysis revealed that RLCs exhibit a specific topographical arrangement. The highest receptor concentrations occur at the ventricular bulges, where their size reaches its maximum in terms of diameter, and at the perivascular pericardial turn-up. The findings suggest that the pericardium is subject to proprioceptive control. RLCs record lateral shearing between the pericardial sublayers, and their distribution pattern enables the detection of distinct dilatation of the heart. Therefore, the pericardium might have an undiscovered function as a sensor with the RLCs as its anatomical correlate.